Tourismpreneurship: Community Empowerment to Strengthen Digital-Based Tourism Economic Synergy in the Tomini Bay Area, Botubarani, Bone Bolango Regency - Haris Danial; Agus Hakri Bokingo; Syahrial Syahrial (International Journal Of Community Service, 2023)
The coastal area is currently a trending spot for tourists who want to enjoy a vacation. Even now travelers are hunting for beach tourism as a diving spot for holidays, including the coast of the Tomini Bay area. Most of the Tomini Bay area is a tourist destination for local and international tourists. However, unfortunately the charm of beach tourism in the Tomini Bay area has not been broadcast nationally or internationally, either in the form of image documentation or cinematic infographics. Therefore, the purpose of this community service is to empower the community in edutourism through English language training and tourism promotion, the beach care movement, and the accessibility of tourism promotion through digital-based and bilingual cinematic infographics (virtual tour). This program is used as an initial step to form a tourism awareness group (POKDARWIS) for the Botubarani community as a form of continuing the program to strengthen the community's economy so that it is not swallowed up by the masses. This program will later form self-help and self-help groups that grow from, by and for the community as a destination for village tourism development, especially the Tomini Bay area. It is hoped that this program will be the first step to deliver Botubarani village as a tourist destination not only on a national scale, but also on an international scale.